ANALISA TEKNIS DAN EKONOMIS PENGGUNAAN COREMAT UNTUK KONSTRUKSI FRP (FIBERGLASS REINFORCED PLASTIC) SANDWICH PADA BADAN KAPAL - Manik, Parlindungan; Hadi, Eko Sasmito (Department of Naval Architecture - Diponegoro University, 2008)
Planning of ship construction is make its having good effectivity value and efficiency. Composite as material alternative to changes of steel feedstock and wood has many applied named FRP (fiberglass reinforced plastics) single skin. The weakness of this FRP was heavy construction and requires many production time. Therefore, will be checked comparison between single skin with sandwich constructions for shell. In this research, the way for making composite is hand lay up method with three various thickness of skin there are : t, t/2, and t/4. To know strength comparison from the various skin of sandwich with single skin, must be test, consist of tensile test.. The result is analyzed then compared by BKI (Biro Klasifikasi Indonesia) rules for the fiberglass ship. Based on the result, indicates that optimization skin thickness of sandwich construction applies Coremat which tensile strength it is equivalent with Single Skin at 2/3t and usage of Sandwich construction causes 23,12 % lighter. In economic analyze, advantage from low weight is compensation of addition 23,12 % DWT. Material cost for Sandwich about 11,35% bigger than Single Skin construction.